Decidability via filtration of neighbourhood models for multi-agent systems - Smith, Clara Patricia; Mendoza, Leandro; Ambrossio, Agustín (2012)
Lately, many multi-agent systems (MAS) are designed as multi-modal systems [9, 15, 23, 22, 26, 28, 18]. Moreover, there are different techniques for combining logics, such as products, fibring, fusion, and modalisation, among others [1, 14, 16]. In this paper we focus on the combination of special-purpose logics for building "on demand" MAS. From these engineering point of view, among the most used normal logics for modeling agents’ cognitive states are logics for beliefs, goals, and intentions, while, perhaps, the most well-known non-normal logics for MAS is the logic of agency (and, possibly, ability). We explore combinations of these normal and non-normal logics. This lead us to handle Scott-Montague structures, (neighbourhood models, in particular) which can be seen as a generalization of Kripke structures [20]. Interested in the decidability of such structures, which is a guarantee of correct systems and their eventual implementations, we give a new presentation for existing theorems that generalize the well-known results regarding decidability through the finite model property via filtrations for Kripke structures. We understand that the presentation we give, based on neighbourhood models, better fits the most accepted and extended logic notation actually used within the MAS community.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Social Turns - SNAMAS @ AISB/IACAP (3ro : 2012 jul. 2-3 : Inglaterra). Social Computing, Social Cognition, Social Networks and Multiagent Systems. pp. 12-17
Keywords: SISTEMAS MULTIAGENTES; LÓGICA COMPUTACIONAL